Implementing Regulation regarding Minority Rights in Romania Special Overview of the Legal Frame of Romanian Law and Constitution - Ghencea, Flavia; Drumea, Mihnea Claudiu (Journal of Economic Development, Environment and People, 2020)
The general concept of non-territorial autonomy is analyzed in the specialized doctrine from various perspectives - considered, in fact, as its attributes – such as, cultural, linguistic, educational, traditional and religious perspectives- all considering the identity of the minority group that lives in a majority community. The present paper, part of a larger research, proposes, on the one hand, an analysis of the legal framework regarding non-territorial autonomy in Romania - from the perspective of the regulations regarding the establishment, organization and functioning of the authorities with their role in the elections and the administrative structures at a local level and, whilst considering the role played by the minority groups in this framework. According to the recently adopted New Administrative Code with big impact on minorities’ lives, another purpose of this research is to track how they are applied to the provisions on the linguistic rights of the national minorities included in Local Public Administrative Regulation. The objectives of this research will be, to use the data obtained in national reports and secondly, to making recommendations on the most efficient way in which the legislative norms regarding the protection of minorities can be applied, focusing on costs, human and financial resources